Chinese foreign relations power and policy since the Cold War - Sutter, Robert G. (Asia in world politics, 2012)
"This comprehensive introduction to Chinese foreign relations examines the opportunities and limits China faces as it seeks growing international influence. Tracing the record of twists and turns in Chinese foreign relations since the end of the Cold War, Robert G. Sutter provides a nuanced analysis that shows that along with popular perceptions of its growing power, Beijing is hampered by both domestic and international constraints. Newly revised, this edition features more extensive treatment of China's role in the international economy and greater discussion of its relations with the developing world. Overall, the text's balanced and thorough assessment shows China's leaders exerting more influence in world affairs but remaining far from dominant. Facing numerous contradictions and tradeoffs, they move cautiously as they deal with a complex global environment."--Publisher's description.